To multiply the polynomials \( (3x - 1)(2x + 4) \), we can use the distributive property (also known as the FOIL method for binomials).
-
Multiply the first terms: \[ 3x \cdot 2x = 6x^2 \]
-
Multiply the outer terms: \[ 3x \cdot 4 = 12x \]
-
Multiply the inner terms: \[ -1 \cdot 2x = -2x \]
-
Multiply the last terms: \[ -1 \cdot 4 = -4 \]
Now, combine all these results: \[ 6x^2 + 12x - 2x - 4 \]
Combine the like terms (12x and -2x): \[ 6x^2 + (12x - 2x) - 4 = 6x^2 + 10x - 4 \]
Thus, the product of the polynomials \( (3x - 1)(2x + 4) \) is: \[ 6x^2 + 10x - 4 \]
So, the final answer is:
- \(x^2\) coefficient: 6
- \(x\) coefficient: 10
- Constant: -4
Therefore, you would fill in:
- \(x^2 + 10x - 4\)